Use of a tin (Sn) flat sheet as a material filter for reduction of scattered gamma photons and enhancement of cold regions image quality in Tc-99m SPECT - Sayed, Inayatullah Shah (MEACSE Publications, 2016)
The presence of scattered gamma photons in SPECT data degrade the quality of reconstructed images. In this work, a material filter was employed in order to improve cold regions detectability and overall image quality by pre-filtering of some fraction of scattered gamma photons. Material filter was constructed from a 300x300mm flat sheet of tin (Sn) 0.25mm thick. It was installed on the outer surface of LEGP collimator of a gamma camera. Tc-99m spectra were plotted from the count rates recorded without and with material filter by scanning a cylindrical source tank in contiguous 10 keV energy windows (55-65, 65-75,……155-165 keV). SPECT image data of R. A. Carlson’s phantom with cold regions insert (placed into the cylindrical tank) were gathered without and with material filter by setting 20% energy window centered at 140 keV. Images were reconstructed by applying filtered back projection method. Tc-99m spectra show the reduction in count rate with material filter from the lower part of the photopeak region <132 keV. Significant decrease in %RMS noise, enhancement of cold regions detectability and significant improvement in contrast of cold regions of diameter 7.3, 9.2 and 11.4 mm at p < 0.05, but, statistically insignificant improvement in contrast of 5.9, 14.3 and 17.9 mm diameter cold regions was achieved with material filter. Findings show that the material filter removes some fraction of scattered gamma photons from image data. Thus, improves SPECT image quality. However, further investigations under clinically realistic conditions require.